2010
DOI: 10.1073/pnas.0906199106
|View full text |Cite
|
Sign up to set email alerts
|

Natural selection in a contemporary human population

Abstract: Our aims were to demonstrate that natural selection is operating on contemporary humans, predict future evolutionary change for specific traits with medical significance, and show that for some traits we can make short-term predictions about our future evolution. To do so, we measured the strength of selection, estimated genetic variation and covariation, and predicted the response to selection for women in the Framingham Heart Study, a project of the National Heart, Lung, and Blood Institute and Boston Univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

17
158
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(180 citation statements)
references
References 30 publications
17
158
2
3
Order By: Relevance
“…Genetic variation in common single nucleotide polymorphisms measured in unrelated individuals also supports this interpretation [34]. Studies by both biologists and demographers also show a moderate genetic component to fertility traits, such as number of children ever born and the age at first birth, which explains up to 40-50% of the variance in these traits [11,[35][36][37][38]. Such findings were also observed for a historical Dutch population [39].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Genetic variation in common single nucleotide polymorphisms measured in unrelated individuals also supports this interpretation [34]. Studies by both biologists and demographers also show a moderate genetic component to fertility traits, such as number of children ever born and the age at first birth, which explains up to 40-50% of the variance in these traits [11,[35][36][37][38]. Such findings were also observed for a historical Dutch population [39].…”
Section: Discussionsupporting
confidence: 61%
“…Recently, Byars et al [11] showed, on the basis of pedigree data, that natural selection was acting on height among United States women: shorter women had higher lifetime reproductive success than taller women, and their descendants were, on average, predicted to be slightly shorter than they would have been in the absence of selection. Stulp et al [12,13] showed phenotypic associations between stature and reproductive success in the United States, such that shorter women had higher reproductive success than their taller counterparts [12], while average height men experienced greater reproductive success than taller or shorter men ( [13]; findings that were replicated by [14] and [15]).…”
Section: Introductionmentioning
confidence: 99%
“…The rate of evolution is the speed at which the characteristics of a population change. For example, a recent study of a contemporary American population found that if the environment of the 1950s and 1960s continued, evolution would lead to a 1.8% decline in total cholesterol levels over a period of five generations [1]. Similarly, the age at menopause would increase by 0.4 years over the same period.…”
Section: Introductionmentioning
confidence: 99%
“…I have not found any studies of humans that employ a model that accounts for overlapping generations. Almost all of these studies rely solely on measures of either the quantity of reproduction such as the average children ever born [6,11], or the number of children surviving to a given age [1,5,7,12,15]. Several studies include values of the long-term growth rates [8,9,13,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Howeveu, in line with uecent ueseauch cultuual and genetic evolution seem to closely inteuact in co-evolutionauy puocesses (Richeuson et a., 2010). Natuual selection is still active on changing tuaits in contempouauy humans (Byaus et al, 2009) by effecting adaptations thuough cultuue -gene coevolution, which may act much fasteu as pueviously thought (Field et al, 2016).…”
mentioning
confidence: 99%